UJI TOKSISITAS AKUT EKSTRAK ETANOL KLIKA JAMBU MEDE (Anacardium occidentale L.) PADA MENCIT JANTAN (Mus musculus) - Faridha Yenny Nonci; Muh Rusdi; Isrul Zul Fajrin La Mohan L (Universitas Islam Negeri Alauddin Makassar, 2014)
Research conducted acute toxicity test of ethanol extract of cashew Klika (Anacardium occidentale L.) in male mice (Mus musculus). This study aims to determine the ethanol extract LD50 Guava Klika Mede supply all oral and toxic symptoms were observed. This study used 25 male mice were divided into five treatment groups. The first group received 0.5% CMC-Na as the control group II, III, IV and V were given sample Klika cashew (Anacardium occidentale L.) with successive doses 40mg/20 gram BB mice, 80mg/20 gram BB mice, 160mg/20 gram BB mice and 320mg/20 gram BB mice. Prior to treatment, the mice were subjected to a prior fasting and received the test substance, in accordance with the calculated dose.The observations of toxic effects based on changes in the behavior of mice such as excessive salivation diarrhea, urinasi, decreased motor activity, aggressive behavior and respiratory changes with time of the successive observation 5, 10. 15, 30, 60, 120, 180 and 240 minutes. For the determination of LD50 values are based on the number of mice in each group died within 24 hours to 7 days. Analysis of data menuntukan toxic effects of the most dominant motion is the effect of the decrease in activity. The results of calculations using the LD50 values obtained Klika Thompson and Weil extract cashew (Anacardium occidentale L.) was 4923.45 mg / KgBB so that the level of toxicity in this category Lu